Private paris ebook - Patterson, James (Private, 2016)
Someone is targeting the most powerful people in Paris . . . and only private investigator Jack Morgan can make it stop. When Jack Morgan stops by Private's Paris office, he envisions a quick hello during an otherwise relaxing trip filled with fine food and sightseeing. But Jack is quickly pressed into a mission: to track down his client's young granddaughter who is on the run from a brutal drug dealer. Before Jack can locate her, several members of France's cultural elite are found dead-murdered in stunning, symbolic fashion. The only link between the crimes is a mysterious graffiti tag. As religious and ethnic tensions simmer in the City of Lights, only Jack and his Private team can connect the dots before the smoldering powder keg explodes.